2000
DOI: 10.2105/ajph.90.7.1100
|View full text |Cite
|
Sign up to set email alerts
|

HIV transmission and the cost-effectiveness of methadone maintenance

Abstract: OBJECTIVES: This study determined the cost-effectiveness of expanding methadone maintenance treatment for heroin addiction, particularly its effect on the HIV epidemic. METHODS: We developed a dynamic epidemic model to study the effects of increased methadone maintenance capacity on health care costs and survival, measured as quality-adjusted life-years (QALYs). We considered communities with HIV prevalence among injection drug users of 5% and 40%. RESULTS: Additional methadone maintenance capacity costs $8200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(54 citation statements)
references
References 153 publications
4
50
0
Order By: Relevance
“…When the problem requires modeling the effect of an intervention on disease spread, methods designed for patient interaction should be selected, such as dynamic transmission models [48,49], DES [50,51], and agent-based models [52]. Similarly, these methods are appropriate when individuals interact with other components of the model, such as use limited resources [53,54]. …”
Section: Conceptualizing the Modelmentioning
confidence: 99%
“…When the problem requires modeling the effect of an intervention on disease spread, methods designed for patient interaction should be selected, such as dynamic transmission models [48,49], DES [50,51], and agent-based models [52]. Similarly, these methods are appropriate when individuals interact with other components of the model, such as use limited resources [53,54]. …”
Section: Conceptualizing the Modelmentioning
confidence: 99%
“…This goal has not been reached in the United States or Canada, despite the demonstrated economic value of that treatment [18-21]. …”
Section: Financial Barriers To Treatmentmentioning
confidence: 99%
“…[18-21] Often the costs of treatment are more than offset by reductions in acquisitive crime (theft or burglary)[20] and in the use of health resources related to transmissions of HIV or hepatitis C.[21] The treatment also results in improvements in health-related quality of life. [22] substitution treatment may be even greater if potential increases in workplace productivity are realized[19], resulting in additional economic benefits outside of the health care sector.…”
mentioning
confidence: 99%
“…While a continuation of the trend towards greater utilization of MMT may result in increased costs to the healthcare system, sustained retention in treatment has been shown to reduce the costs of acquisitive crime and may avert potential health care costs attributable to infectious diseases like HIV and Hepatitis C (Alter and Liang, 2012; US Food and Drug Administration, 2002). As a result, prior studies have shown MMT to be highly cost-effective, if not cost-saving (Nosyk et al, 2012; Zaric et al, 2000; Rosenblum et al, 2003). Further research is required to quantify the cumulative effects of repeated detoxification, compared to the current standard of care (MMT) in terms of morbidity, mortality, and incremental costs to society.…”
Section: Discussionmentioning
confidence: 99%